Evaluation of liver function in patients with liver cirrhosis and chronic liver disease using functional liver imaging scores at different acquisition time points - Tang, Guixiang; Liu, Jianbin; Liu, Peng; Huang, Feng; Shao, Xunuo; Chen, Yao; Xie, An (Frontiers in Genetics, 2022)
Purpose: This paper aims to explore whether functional liver imaging score (FLIS) based on Gd-EOB-DTPA-enhanced magnetic resonance imaging (MRI) images at 5, 10 and 15 min can predict liver function in patients with liver cirrhosis or chronic liver disease and its association with indocyanine green 15-min retention rate (ICG-R15), Child-Pugh (CP) score, albumin-bilirubin (ALBI) score, and model for end-stage liver disease (MELD) score. Methods: This study included 110 patients with chronic liver disease (CLD) or liver cirrhosis (LC) (93 men, 17 women; mean±standard deviation=56.96±10.16) between July 2019 and May 2022. The relationship between FLIS and three FLIS quality scores and the degree of liver function were evaluated using Spearman’s rank correlation coefficient. The ability of FLIS to predict hepatic function was investigated using receiver operating characteristic (ROC) curves. Results: Intra- and inter-observer intraclass correlation coefficients (ICCs) for FLIS at each time point indicated excellent agreement. At each time point, FLIS had a moderate negative association with liver function classification (r=[-0.641]-[-0.428], p<0.001), and weak to moderate correlation with some other clinical parameters except for creatinine (p>0.05). FLIS showed moderate discriminatory ability between different liver function levels. The area under the ROC curves (AUCs) of FLIS at 5, 10 and 15 min after enhancement to predict ICG-R15 of 10% or less were 0.838, 0.802 and 0.723, respectively; those for predicting ICG-R15 greater than 20% were 0.793, 0.824 and 0.756, respectively; those for predicting ICG-R15 greater than 40% were 0.728, 0.755 and 0.741, respectively; those for predicting ALBI grade 1 were 0.734, 0.761 and 0.691, respectively; those for predicting CP class A cirrhosis were 0.806, 0.821 and 0.829, respectively; those for predicting MELD score of 10 or less were 0.837, 0.877 and 0.837, respectively. No significant difference was found in the AUC of FLIS at 5, 10 and 15 min (p>0.05). Conclusion: FLIS presented a moderate negative correlation with the classification system of hepatic function at a delay of 5, 10 and 15 min. In addition, the use of FLIS to evaluate liver function can reduce the observation time of the hepatobiliary period.